Impulse Buying On Green Products An Approach To Enhance Product Competitiveness - Baghebany, Alireza (2010)
This research was planned to understand impulse buying behavior and it\'s dimension in Malaysia society. Since impulse buying has been a large portion of consumers purchasing behavior and has brought a significant source of revenue for sellers, it has been noticed by researchers in concumer behavior. This study also examined on consumer impulse buying for \"green\" products.